Awareness of Pre-Graduating Female Students Concerning Early Detection of Breast Cancer at University of Kerbala, Iraq in 2025 - Hadeel Rasheed Seger; Taher Mohsin Al-Fahham; Hussein Khleif Kitab (Al-Turath Journal of Nursing, 2026)
Background: Breast cancer is a major killer in women globally and in developing regions where the early cancer detection facilities are unavailable. Awareness would be a tool to fight this disease through early detection and there by decrease the morbidity and mortality. This study aimed to assess the awareness of pre graduating female students regarding early detection of breast cancer at University of Kerbala in Iraq. Methods: A cross- sectional design was conducted from 27th January 2024 to May 2025 at Kerbala University. A non-probability, quota sampling was used to select 100 pre graduating female students. The tool used in this study comprised of two parts: demographic characteristics and students' awareness regarding early detection of breast cancer. Valid and reliable questionnaire was used to collect data. Results: The most of female students were pre graduated from humanity colleges, with age group of (21-24) years. The level Awareness of female students regarding early detection of breast cancer was moderate. There is a statistically significant relationship between college classification and their awareness, also There is a significant relationship among the level of awareness and family history of breast cancer, and clinical breast examination experience. Conclusion: The moderate awareness levels observed among female students, coupled with significant deficiencies in key areas of breast cancer detection knowledge. There was a significant relationship between type of college and students' awareness. Add Educational program to educate students about new screening procedure and its importance for breast cancer screening.